2011
DOI: 10.1530/eje-11-0430
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous subclinical thyroid disorders, physical and cognitive function, depression, and mortality in older individuals

Abstract: Objective: To what extent endogenous subclinical thyroid disorders contribute to impaired physical and cognitive function, depression, and mortality in older individuals remains a matter of debate. Design: A population-based, prospective cohort of the Longitudinal Aging Study Amsterdam. Methods: TSH and, if necessary, thyroxine and triiodothyronine levels were measured in individuals aged 65 years or older. Participants were classified according to clinical categories of thyroid function. Participants with ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 41 publications
6
109
0
5
Order By: Relevance
“…de Jongh et al found in the same population we used that subclinical thyroid disorder does not correspond with disadvantageous effects on the physical and cognitive functions of the elderly. However, the group of subclinical hypo-and hyperthyroid persons was relatively small in comparison with the euthyroid group (37).…”
Section: Discussionmentioning
confidence: 82%
“…de Jongh et al found in the same population we used that subclinical thyroid disorder does not correspond with disadvantageous effects on the physical and cognitive functions of the elderly. However, the group of subclinical hypo-and hyperthyroid persons was relatively small in comparison with the euthyroid group (37).…”
Section: Discussionmentioning
confidence: 82%
“…However, data from a cross-sectional study in Australia indicate that subclinical thyroid disease in women (18-75 years) of one community was not associated with decreased well-being or impaired health -related quality of life (127) (A). Furthermore, other large cross-sectional studies have also failed to find any significant effects on cognition, depression and anxiety in SH (38,99,128,129) (D,A,A,B). To add more controversy to this topic, two studies from Brazil exploring neuropsychological function by different techniques arrived at opposite conclusions (130,131) (B,B).…”
Section: Are Clinical Symptoms Depression and Cognitive Dysfunctionmentioning
confidence: 93%
“…There is good evidence suggesting that SH is not related to symptoms or with disorders of cognition and mood in older persons (99,128,129) (A,B,B), and there is strong evidence (133,134) (A,A) against treating elderly patients with SH aiming to improve cognitive function, quality of life and symptoms.…”
Section: Should Elderly Patients Be Considered For Treatment?mentioning
confidence: 99%
“…Additional analysis stratified by the degree of serum TSH elevation (4.5-6.9; 7.0-9.9 and 10.0-19.9 mIU/l) confirmed the absence of this association [22]. Accordingly, a cross-sectional study with subgroup analyses by age evidenced an increased CHD risk only in younger sHT participants (<50 years old) [23]. Moreover, a meta-analysis of 5 studies demonstrated that sHT is associated with increased CHD prevalence and events only in young adults (aged <65 years), in which an increased incidence of CHD was present regardless the degree of serum TSH elevation [24].…”
Section: Editorialmentioning
confidence: 65%